Convert following infix expression to the prefix expression.
a - b + c * (d / e - (f + g))
Answers were Sorted based on User's Feedback
Answer / elle
a-b+c*(d/e-(f+g))
=a-b+c*(/de-(+fg))
=a-b+c*(T-S) where T=/de,S=+fg
=a-b+c*-(TS)
=-ab+c*-(TS)
=-ab+c*V where V=-TS
=-ab+*cV
=X+Y where X=-ab,*cV=Y
=+XY
=+-ab*cV
=+-ab*c-TS
=+-ab*c-/de+fg
Is This Answer Correct ? | 41 Yes | 7 No |
Answer / bipin from utkal university mc
a-b+c*(d/e-(f+g))
a-b+c*(d/e-(+fg))
a-b+c*(/de-(+fg))
a-b+c*(-/de+fg)
a-b+(*c-/de+fg)
-ab+(*c-/de+fg)
+-ab*c-/de+fg (final answer)
Is This Answer Correct ? | 34 Yes | 5 No |
Answer / tadveer verma
a-b+c*(d/e- (+fg))
a-b+c*(/de - +fg)
a-b+c* -/de+fg
a-b+ *c-/de+fg
-ab + *c-/de+fg
+-ab*c-/de+fg
Is This Answer Correct ? | 13 Yes | 2 No |
Answer / lucky
a-b+c*(d/e-(f+g))
a-b+c*(d/e-+fg)
a-b+c*-d/e+fg
a-b+c*-/de+fg
a-b+*c-/de+fg
+a-b*c-/de+fg
+-ab*c-/de+fg
Is This Answer Correct ? | 14 Yes | 4 No |
Answer / madhu
a-b+c*(d/e-(f+g))
a-b+c*(d/e-+fg)
a-b+c*(/de-+fg)
a-b+c*-/de+fg
a-b+*c-/de+fg
-ab+*c-/de+fg
+-ab*c-/de+fg
Is This Answer Correct ? | 11 Yes | 4 No |
Answer / bipin fro uu mca
a-b+c*(/de-(+fg))
a-b+c*(-/de+fg)
a-b+*c-/de+fg
-ab+*c-/de+fg
+-ab*c-/de+fg
Is This Answer Correct ? | 8 Yes | 2 No |
Why is concurrenthashmap thread safe?
Differentiate between failfast and failsafe.
What is raid (redundant array of inexpensive disks)? Explain its level?
Is arraylist a list?
Can hashmap be sorted?
Difference between arrays and linked list?
Why linked list is required?
What is default array size?
Is radix sort stable?
What is immutablelist?
Why hashmap is faster than hashset?
do records fall under linear or non linear data structures?